2020
DOI: 10.3390/molecules25173837
|View full text |Cite
|
Sign up to set email alerts
|

Hypobaric Packaging Prolongs the Shelf Life of Refrigerated Black Truffles (Tuber melanosporum)

Abstract: Black truffle (Tuber melanosporum Vitt.) is a fine agro-food product known for its unique aroma and very limited shelf life (maximum of 5–7 days, room temperature). Hypobaric packaging at 30 kPa, a mix of 1% O2/99% N2, and 40% CO2/60% N2 were studied to prolong the shelf life of black truffle at 4 °C in sealed polypropylene vessels, compared to normal atmosphere. Epiphytic microbial population, firmness, weight loss, CO2 formation, and sensory properties were monitored weekly up to 35 days of storage and were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…The decrease of 1‐octen‐3‐ol after 90 days (Table 4) is most likely due to truffle degradation, which was also supported by Savini et al. (2020). Another study investigating the volatile changes in T. magnatum under accelerated storage at 23°C reported that methional did not significantly reduce with storage time (Niimi et al., 2021), which is contradictory to our observation (Table 4).…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…The decrease of 1‐octen‐3‐ol after 90 days (Table 4) is most likely due to truffle degradation, which was also supported by Savini et al. (2020). Another study investigating the volatile changes in T. magnatum under accelerated storage at 23°C reported that methional did not significantly reduce with storage time (Niimi et al., 2021), which is contradictory to our observation (Table 4).…”
Section: Resultssupporting
confidence: 77%
“…A previous study by Savini et al. (2020) reported an increase in ethyl‐3‐methylbutanoate throughout 35 days of refrigerator storage under different packaging conditions, and this phenomenon was related to the decay of fresh black truffles. The decrease of 1‐octen‐3‐ol after 90 days (Table 4) is most likely due to truffle degradation, which was also supported by Savini et al.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Regarding the industry, another critical factor affecting truffle aroma is the preservation method used. Various processing and preservation techniques are typically used in the industry to protect aroma and help prolong their shelf life after harvest such as freeze-drying [ 56 , 57 ], refrigeration [ 58 ], irradiation [ 59 ], modified atmosphere packaging (MAP) with microperforated films [ 60 ], and Treatment combination (MAP, electron-beam irradiation, refrigeration) [ 61 , 62 , 63 ]. With the recent progress in food technology, more innovative ways are expected to preserve truffles whilst maintaining their sensory and biochemical properties.…”
Section: Truffle Aroma Characterization: Black Truffle and White Tmentioning
confidence: 99%